Reducing Anxiety Levels With Guided Imagery In Pre Operative Patients With General Anesthesia Techniques - Ika Husnul Mar'a; Vidya Urbaningrum; Muh. Nur Syamsu; Cicilia Nony Ayuningsih Bratajaya (Poltekkes Kemenkes Kupang, 2026)
Background: Anxiety is a common psychological response experienced by patients in the preoperative phase, especially those undergoing surgery under general anesthesia. Efforts to reduce anxiety can be done through non-pharmacological approaches, including guided imagery. Objectives: This study aimed to determine the effect of guided imagery on reducing anxiety in preoperative patients undergoing general anesthesia at Bekasi Regency Hospital. Methods: This study employed a quantitative method with a pre-experimental design using a one-group pretest–posttest design. A total of 47 respondents were selected using a purposive sampling technique. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) was used to evaluate respondents' anxiety levels before and after the intervention. The guided imagery lasted for 10 minutes. Data evaluation included univariate and bivariate analyses, with the nonparametric Wilcoxon test used to test hypotheses. Results: This study demonstrated a decrease in preoperative anxiety levels in patients after receiving guided imagery intervention. Based on the Wilcoxon test results, a p-value of 0.000 indicated that the intervention significantly reduced patient anxiety. Conclusions: That there is an effect after being given guided imagery intervention on reducing anxiety levels in pre-operative patients with general anesthesia techniques.